Asymmetric Synthesis of Alkyl Fluorides: Hydrogenation of Fluorinated Olefins. Issue 27 (17th May 2019) - Ponra, Sudipta; Yang, Jianping; Kerdphon, Sutthichat; Andersson, Pher G.
Abstract: The development of new general methods for the synthesis of chiral fluorine‐containing molecules is important for several scientific disciplines. We herein disclose a straightforward method for the preparation of chiral organofluorine molecules that is based on the iridium‐catalyzed asymmetric hydrogenation of trisubstituted alkenyl fluorides. This catalytic asymmetric process enables the synthesis of chiral fluorine molecules with or without carbonyl substitution. Owing to the tunable steric and electronic properties of the azabicyclo thiazole‐phosphine iridium catalyst, this stereoselective reaction could be optimized and was found to be compatible with various aromatic, aliphatic, and heterocyclic systems with a variety of functional groups, providing the highly desirable products in excellent yields and enantioselectivities. Abstract : A general method for the synthesis of enantioenriched alkyl fluorides is based on the iridium‐catalyzed asymmetric hydrogenation of different trisubstituted alkenyl fluorides. This catalytic process enables the synthesis of diverse chiral organofluorine compounds with or without carbonyl substitution and with different electronic properties in excellent yields and enantioselectivities.